Selves and Subjectivities: Reflections on Canadian Arts and Culture - Manijeh Mannani and Veronica Thompson (Athabasca University Press, 2012)
Long a topic of intricate political and social debate, Canadian identity has come to be understood as fragmented, amorphous, and unstable, a multifaceted and contested space only tenuously linked to traditional concepts of the nation. As Canadians, we are endlessly defining ourselves, seeking to locate our sense of self in relation to some Other. By examining how writers and performers have conceptualized and negotiated issues of personal identity in their work, the essays collected in Selves and Subjectivities investigate emerging representations of self and other in contemporary Canadian arts and culture. Included are essays on iconic poet and musician Leonard Cohen, Governor General award